Criteria for the authorisation of specialty training for competence in internal medicine and rheumatology: a position paper of the German Society for Rheumatology and Clinical Immunology = Kriterien für die Weiterbildungsbefugnis zur Facharztkompetenz Innere Medizin und Rheumatologie : ein Positionspapier der Deutschen Gesellschaft für Rheumatologie und Klinische Immunologie - Pfeil, Alexander; Fleck, Martin; Aringer, Martin; Baraliakos, Xenofon; Ernst, Diana; Haase, Isabell; Hillebrecht, Christiana; Hoyer, Bimba Franziska; Keyßer, Gernot; Kötter, Ina; Krause, Andreas; Krusche, Martin; et al. (Zeitschrift für Rheumatologie, 2025)
The model advanced training regulations define the content of advanced training to achieve the qualification of medical specialist in all specialties and sub-specialties of medicine. As rheumatology is one of the ten specialties for internal medicine in Germany, regulations cover basic competencies of general and all other specialties in internal medicine as well as special skills in rheumatology. There are currently no criteria for issuing the authorization in advanced training. This position paper describes the criteria proposed by the German Society for Rheumatology and Clinical Immunology (DGRh), which should be the foundation for the issuance of authorization for advanced training in the field of internal medicine and rheumatology and for the assessment of the duration. The model advanced training regulations 2018 and the advanced training plan recommended by experts function as the basis for this. Based on the criteria, the authorization for advanced training to advanced specialist training in internal medicine and rheumatology can be allocated in a standardized, graded and transparent manner throughout Germany. This enables an optimal quality of advanced training in rheumatology, which can be adapted to the future developments in the discipline.